First insights into the gut microbiome of Diatraea saccharalis: From a sugarcane pest to a reservoir of new bacteria with biotechnological potential - Puentes-Cala, Edinson; Atehortúa-Bueno, María; Tapia-Perdomo, Valentina; Navarro-Escalante, Lucio; Hernández-Torres, Jorge; Castillo-Villamizar, Genis (Frontiers in Ecology and Evolution, 2023)
A country's biodiversity is a key resource for the development of a sustainable bioeconomy. However, often the most biodiverse countries on the planet hardly profit from their biological diversity. On the contrary, occasionally components of that biodiversity become a threat to society and its food sustainability. That is the case of the sugarcane borer Diatraea saccharalis. Here, the analysis of the bacteria associated with the digestive tract of D. saccharalis reveals a rich and diverse microbiota. Two types of diets were analyzed under laboratory conditions. The metataxonomic analysis revealed a number of taxa common to most of the larval pools analyzed with relative abundances exceeding 5%, and five families of bacteria which have also been reported in the gut of another Lepidoptera. A large fraction of microorganisms detected by amplicon sequencing were considered to be rare and difficult to cultivate. However, among the cultivable microorganisms, 12 strains with relevant biotechnological features were identified. The strain that showed the highest cellulolytic activity (GCEP-101) was genome sequenced. The analysis of the GCEP-101 complete genome revealed that the values of 16S rRNA identity, the Average Nucleotide Identity, and the digital DNA-DNA hybridization place the strain as a candidate for a new species within the genus Pseudomonas. Moreover, the genome annotation of the putative new species evidenced the presence of genes associated with cellulose degradation, revealing the hidden potential of the pest as a reservoir of biotechnologically relevant microorganisms.